Humidity-Tolerant Single-Stranded DNA-Functionalized Graphene Probe for Medical Applications of Exhaled Breath Analysis - Jung, Youngmo; Moon, Hi Gyu; Lim, Chaehyun; Choi, Keunsu; Song, Hyun Seok; Bae, Sukang; Kim, Soo Min; Seo, Minah; Lee, Taikjin; Lee, Seok; Park, Hyung-Ho; Jun, Seong Chan; et al. (WILEY-V C H VERLAG GMBH, 2017)
Highly sensitive and selective chemiresistive sensors based on graphene functionalized by metals and metal oxides have attracted considerable attention in the fields of environmental monitoring and medical assessment because of their ultrasensitive gas detecting performance and cost-effective fabrication. However, their operation, in terms of detection limit and reliability, is limited in traditional applications because of ambient humidity. Here, the enhanced sensitivity and selectivity of single-stranded DNA-functionalized graphene (ssDNA-FG) sensors to NH3 and H2S vapors at high humidity are demonstrated and their sensing mechanism is suggested. It is found that depositing a layer of ssDNA molecules leads to effective modulation of carrier density in graphene, as a negative-potential gating agent and the formation of an additional ion conduction path for proton hopping in the layer of hydronium ions (H3O+) at high humidity (>80%). Considering that selectively responsive chemical vapors are biomarkers associated with human diseases, the obtained results strongly suggest that ssDNA-FG sensors can be the key to developing a high-performance exhaled breath analyzer for diagnosing halitosis and kidney disorder.
Keywords: GAS SENSOR; SURFACE; DESIGN; FILMS; OXIDE; NANOPARTICLES; FABRICATION; SOLUBILITY; ADSORPTION; BIOMARKERS